2023
DOI: 10.3390/molecules28073148
|View full text |Cite
|
Sign up to set email alerts
|

Elderberry Extracts: Characterization of the Polyphenolic Chemical Composition, Quality Consistency, Safety, Adulteration, and Attenuation of Oxidative Stress- and Inflammation-Induced Health Disorders

Abstract: Elderberry is highly reputed for its health-improving effects. Multiple pieces of evidence indicate that the consumption of berries is linked to enhancing human health and preventing or delaying the onset of chronic medical conditions. Compared with other fruit, elderberry is a very rich source of anthocyanins (approximately 80% of the polyphenol content). These polyphenols are the principals that essentially contribute to the high antioxidant and anti-inflammatory capacities and the health benefits of elderbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 165 publications
0
12
0
Order By: Relevance
“…The fruits and flowers of SN and SE are rich in bioactive phenolics including phenolic acids, flavonoids, and anthocyanins, which underlie their health benefits, supported by strong scientific evidence [14][15][16]. They act as antioxidants, reduce inflammation, modulate the immune system, demonstrate activity against cancer, and exhibit a broad spectrum of antiviral properties [14][15][16][17][18][19][20][21][22][23]. Extracts and products from SN fruits that exhibit antiviral activity are currently some of the most significant highlights of research [24].…”
Section: Introductionmentioning
confidence: 99%
“…The fruits and flowers of SN and SE are rich in bioactive phenolics including phenolic acids, flavonoids, and anthocyanins, which underlie their health benefits, supported by strong scientific evidence [14][15][16]. They act as antioxidants, reduce inflammation, modulate the immune system, demonstrate activity against cancer, and exhibit a broad spectrum of antiviral properties [14][15][16][17][18][19][20][21][22][23]. Extracts and products from SN fruits that exhibit antiviral activity are currently some of the most significant highlights of research [24].…”
Section: Introductionmentioning
confidence: 99%
“…3 ). High total phenolic content have been previously reported from elderberries ( Liu et al, 2022 ; Osman et al, 2023 ) and have been suggested to be the major reason for the berries purported health benefits ( Ferreira et al, 2022a , 2022b ; Liu et al, 2022 ). The vast majority of these phenolic acids were identified as (5- or 3-) caffeoylquinic acid, more commonly known as chlorogenic and neochlorogenic acids (CQA).…”
Section: Resultsmentioning
confidence: 81%
“…Therefore, a key regulator of testosterone production is the scavenging of intracellular ROS. Many studies, including Ferreira et al (2022), have reported intracellular ROS scavenging by elderberry extract [ 39 41 ]. Scavenging of intracellular ROS by elderberry extract has been reported in many research papers Ferreira et al (2022) [ 39 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies, including Ferreira et al (2022), have reported intracellular ROS scavenging by elderberry extract [ 39 41 ]. Scavenging of intracellular ROS by elderberry extract has been reported in many research papers Ferreira et al (2022) [ 39 41 ]. On the other hand, our study is about the ROS inhibitory effect of FL, a monosaccharide amino acid, which is not an anthocyanin component.…”
Section: Resultsmentioning
confidence: 99%